Punt : die Suche nach dem 'Gottesland' - Breyer, Francis. (Culture and History of the Ancient Near East, 2016)
Francis Breyer's Punt. Die Suche nach dem ›Gottesland‹ covers every aspect concerning Punt, this land known only from ancient Egyptian sources. Several disciplines have contributed to the discussion on its localization: Egyptology, Nubien Studies, Botany, Zoology, Anthropology, and African Studies, among others. The various disciplines' arguments are carefully studied, especially with the history of research and the Zeitgeist in mind. For the very first time, the question is asked, which archaeological culture from the horn of Africa can be correlated to the data from the textual and iconographic sources, all of which are collected, translated and commented on. Breyer not only comprehensively reconstructs the entire organization of the Egyptian expeditions, id est participants, routes, trade goods, but also addresses the people of Punt, their cultural background and way of life.